Perception of the risk of SARS CoV-2 infection among 1st year Health Professions students: a qualitative study. - Bandini, Stefania; Rossi, Elena; Montalti, Matteo; Martinelli, Stefano; Sacchetti, Cleta; Gaddoni, Claudio; Deserri, Deborah; Valentini, Orietta (Acta Biomedica Atenei Parmensis, 2024)
Background and aim: The 1st Academic Year students of health professions degree courses of the University of Bologna carried out the curricular internship according to the teaching system during the pandemic period. The objective was to identify the elements determining the perception of the risk of SARS-CoV-2 infection both before and after the internship experience, with the aim of identifying the experience of the elements determining the risk of infection and the behaviours adopted for the management of the risk of SARS-CoV-2 infection in the pandemic context.Methods: it is a descriptive qualitative study with convenience voluntary recruitment; for data collection, focus groups were carried out both before and after the internship experience.Results: it emerged that the pandemic was not an obstacle to the internship, that was perceived as an opportunity for growth and development of the chosen profession; students were not afraid of getting infected by COVID-19, they felt responsible for preventive behaviours and the use of Personal Protective Equipment and Medical Device; anxiety and fear levels were very reduced and in any case decreased in a short time since the beginning of the internship.Conclusions: further study developments could be aimed at assessing the perception of the risk of infection in the real context and with the use of prevention and protection measures.